National Manpower and Youth Council implications for Thailand - Sanguanshua, Wit 1942-; Philippines (Republic) National Manpower and Youth Council ([Quezon City s.n.], 1973)
The objectives of the NYMC are (1) to formulate integrated comprehensive, long-term plans for efficient allocation, accelerated development, and optimum utilization of manpower and out-of-school youth for economic and industrial growth; and (2) to establish a National Manpower Skills Center and regional and local training centers for gainful occupational skills. The Council has 14 members: 8 government officials and 6 from private sector. The Secretary of Labor and the Secretary of Education are Chairman and Vice-Chairman, respectively. The Secretariat under a Director-General implements NMYC programs through its Office of Manpower Development, Office of Out-of-School Youth Development, and the National Manpower Skills Center. Its activities, programs and projects include the Accelerated Manpower Training Program, Re-Structured Manpower Training Program, Instructor's Training Course, Trainers Training Course, Bayanihan Youth Settlement, Livestock and Poultry, Cooperative Settlement Training Project, and the National Agricultural Skills Training.
Thesis (M.Ed.)--University of the Philippines.